"Peli so jih mati moja ---" - Stanonik, Marija (Traditiones (Ljubljana), 1999)
Based on written, oral and literary sources, the article deals with the 20th century singing culture of the Ziri basin. The area around Ziri represents a juncture of the Alpine, the Dinaric and the Mediterranean regions. The most reliable data in the article is that on the singing repertory of the area.
Keywords: Ethnopoetics; ljudske pesmi; slovstvena folklora; Slovene literature; slovenska književnost